ISLAMIC EDUCATION MANAGEMENT IN THE 21ST CENTURY: CHALLENGES AND OPPORTUNITIES - Loso Judijanto; Al-Amin (International Journal of Teaching and Learning, 2025)
This research examines Islamic education management in the context of the 21st century, focusing on the challenges and opportunities faced. In the era of globalisation and technological revolution, Islamic education is required to adapt without losing the essence of its fundamental values. This study uses the literature analysis method. The results show that the main challenges include: (1) the need for technology integration in learning, (2) demands for curriculum development relevant to global needs, (3) improving the quality and competence of teaching staff, and (4) competition with secular education systems. Meanwhile, the opportunities identified include: (1) expansion of Islamic education through digital platforms, (2) strengthening the global Islamic education network, (3) developing educational models that integrate Islamic values with 21st century skills, and (4) increasing the competitiveness of graduates in the international labour market. The study concludes that 21st century Islamic education management requires a holistic and innovative approach, with an emphasis on flexibility, quality and relevance. Proposed recommendations include curriculum reform, investment in educational technology development, capacity building of teaching staff, and strengthening international co-operation in Islamic education.